The Implementation of Genre-Based Approach Using Visual Media in Teaching Descriptive Writing - Silfi Selfia Putri; Bambang Ruby Sugiarto; Luthfiyatun Thoyyibah (Journal of English Education Program (JEEP), 2026)
This study was carried out to examine the use of visual media integrated into Genre-Based Approach (GBA) for teaching students how to write descriptive texts. Conducted at an Islamic Senior High School in Tasikmalaya, the researcher involved one English teacher and nine students from class XI IPA as participants. The present study used qualitative case study with non- participatory observation and interview instruments To analyze observations, researcher used several procedures such as collecting information, selecting the main data, presenting relevant data, verifying, and concluding the research results. Meanwhile, the interview results were analyze using thematic analysis. The first conclusion revealed that the teacher consistently implemented all stages of GBA by utilizing visual media in the form of pictures to stimulate ideas and build students' understanding in learning to write descriptive texts in class. Then the second conclusion revealed that students gave positive responses to the approach. They were helped in adding vocabulary, developing ideas, and understanding the structure of descriptive text. However, this study also discovered that some learners still faced challenges with grammar, especially in selecting appropriate tenses and applying correct subject-verb agreement in accordance with the rules of descriptive text. Therefore, for future research, it is recommended to complete and overcome the weaknesses of this study, and more focused on grammatical aspects and developing more varied media.